Auditors' perceptions of the impact of continuous auditing on the quality of Internet reported financial information in Egypt. Issue 1 (4th January 2016) - Amin, Hala M. G.; Mohamed, Ehab K. A.
Abstract : Purpose: – The purpose of this paper is to explore the perceptions of auditors in Egypt toward the role that continuous auditing (CA) can play in offsetting the challenges facing the quality of Internet-reported financial information. The paper also examines the impact of audit firm type and years of experience on these perceptions. Design/methodology/approach: – Ninety-six auditors working in the Big 4 and large local audit firms are surveyed to attain their perceptions on the issues examined. Chi-square, Mann–Whitney and t -test are used to test the research hypotheses. Findings: – The overall results indicate that the majority of auditors in Egypt agree that implementing CA can offset the challenges associated with the Internet financial reporting (IFR) environment. The results also reveal that there are significant differences between auditors working in Big 4 audit firms and those working in local firms regarding the perceptions of the effect of CA on some aspects of the timeliness of information. Research limitations/implications: – The paper extends the stream of research on both CA and IFR that confirms that the widespread use of the Internet in disclosing financial information continues to be a worrisome problem for auditing firms. Practical implications: – The paper provides insights into the challenges facing auditing in the IFR environment and how implementing CA can help offset these challenges. Originality/value: – To the best of our knowledge, this paper is the first to examine issues related to CA in the IFR environment in the Middle East and, in particular, Egypt.